2017
DOI: 10.5812/numonthly.42507
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Voiding Habits on Uroflowmetry in Childhood

Abstract: Background: Urodynamic studies (UDS) is a simple non-invasive test to assess lower urinary tract function but it may be affected by several factors includes age, sex, voiding volume and voiding position. These interventional parameters become more highlighted while performing UDS in children whose emotional stress control and coping with unfamiliar situation is more difficult. Methods: Seventy six primary school age healthy children underwent screening uroflowmetry in different voiding positions voluntarily. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 8 publications
(12 reference statements)
1
5
0
Order By: Relevance
“…In recent studies, it has been reported that UFM values of the age group of 11-15 years differ significantly when compared with the lower age groups, and therefore the children have been divided into age groups in terms of UFM results. 19,26,28,30,31,39 Our results were similar to other studies, and the Qmax and Qavg values in girls were significantly higher than in boys in both age groups. This finding has been related to the increase in VV with age and the proportionality of urine flow rate with increasing VV.…”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…In recent studies, it has been reported that UFM values of the age group of 11-15 years differ significantly when compared with the lower age groups, and therefore the children have been divided into age groups in terms of UFM results. 19,26,28,30,31,39 Our results were similar to other studies, and the Qmax and Qavg values in girls were significantly higher than in boys in both age groups. This finding has been related to the increase in VV with age and the proportionality of urine flow rate with increasing VV.…”
Section: Resultssupporting
confidence: 91%
“…Some studies suggest higher VVs in girls than in boys, 13,28 while others disagree. 39 A study comparing VVs in children using different toilet styles found significantly higher VVs with Turkish-style toilets. 39 In our study, girls had a slightly lower mean VV than boys, but the difference was not statistically significant.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations